Ghana’s economic and agricultural transformation: Past performance and future prospects - Diao, Xinshen; Hazell, Peter B. R.; Kolavalli, Shashidhara; Resnick, Danielle (International Food Policy Research Institute, 2019)
Ghana’s Economic and Agricultural Transformation: Past Performance and Future Prospects explores the challenges and opportunities of Africa’s transformation through an integrated economic and political analysis. Using Ghana as a case study, a wide range of primary and secondary data used to look at the potential of urbanization, the role of public investments, government support for value chain development, and government commitment to agriculture sector transformation. Agriculture offers real options for transformation, and this book examines the viability of those options given political-economy constraints, past investment decisions, and the broader global environment in which Ghana, and Africa, must now compete.